Similarity in Analytic Behavior Intermediate Radial States of the Hydrogen Atom & Production of Radionuclides and Gamma Decay - Pishkoo, Amir (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The purpose of this paper is to show that analytic behavior of ground and intermediate states of the Hydrogen atom is similar to Gamma decay in molybdenum-99 (99mTc â†’ 99Tc + Î³).